International trade through the prism of statistics: problems of accounting, evaluation and analysis - N. E. Grigoruk; G. A. Galkin (Vestnik MGIMO-Universiteta)
In economic research, much attention is traditionally paid to the issues of trade and economic cooperation between states and the development of international trade. This kind of research is based on the materials of official statistics of countries and international organizations, which are not always published on a comparable basis, making it difficult, and sometimes impossible to do an objective analysis of processes taking place both in bilateral economic relations and in international trade in general. The article deals with this important problem of comparability of statistical sources.Using a large amount of factual and statistical material, the authors trace the changes that have occurred in world trade relations of the 21st century, paying special attention to the post-crisis period, they reveal the main features of the geographical and commodity structure of trade, they present a comparative analysis of the rates of development of world exports and imports by groups of countries, assess Russia's participation in international trade, and also demonstrate the methodological content of the main statistical indicators that are used to characterize foreign economic relations.For many decades, international cooperation in the field of statistics has focused on the problem of unifying information on the foreign economic activity of countries. Solving this problem, the UN Statistical Commission has drawn up methodological documents, which are usually called "international statistical standards". Based on the study of these documents, as well as materials of official statistics of countries and other primary sources, the authors characterize the process of international standardization of information on foreign economic relations of countries. The article presents a critical analysis of the key provisions of the latest methodological standards of statistics, considers the practice of their application in countries, including the Russian Federation, identifies the main achievements and problems in this area.